CALR-ETdb, the database of calreticulin variants diversity in essential thrombocythemia. (2nd January 2022) - El Jahrani, Nora; Cretin, Gabriel; de Brevern, Alexandre G.
Abstract: Essential thrombocythemia (ET) is a blood cancer defined by a strong increase of platelet numbers. A quarter of patients suffering from ET show mutations in the last exon of calreticulin (CALR) gene. Two variants named type 1 and type 2 represent 85% of these patients. However, a large number of other variants have been determined. In this study, we have compiled variants taken from COSMIC database and literature leading to 155 different variants. This large number of variants allowed redefining 5 new classes extending the classification of type 1-like and type 2-like to a finer description. These analyses showed that last class, named E, corresponding to more than 10% of CALR variants seemed not attached to ET. Structural properties analyzed showed that CALR variants associated to ET have common features. All the compiled and refined information had been included into a freely dedicated database CALR-ETdb (https://www.dsimb.inserm.fr/CALR-ET ). Graphical Abstract: uf0001